Effect of Tai Chi Yunshou training on the balance and motor functions of stroke patients: a systematic review and meta-analysis of randomized controlled trials - Zhang, Liying; Zhang, Lijuan; Yu, Xiaoming; Zhou, Huanxia; Ding, Yuwu; Wang, Jiening (Frontiers in Neurology, 2023)
Background There is insufficient evidence on the effect of Tai Chi Yunshou on improving balance and motor function in stroke survivors. Therefore, this systematic review and meta-analysis aimed to evaluate the effect of Tai Chi Yunshou on improving balance and motor function in stroke patients through a comprehensive literature search. Methods English and Chinese databases were searched from inception to February 10, 2023, to collect randomized controlled trials (RCTs) investigating the effects of Tai Chi Yunshou on balance and motor function in stroke survivors. Two reviewers independently selected studies meeting eligibility criteria, extracted required data, and assessed the risk of bias using methods recommended by the Cochrane Reviewers’ Handbook. Primary outcomes were balance function and motor function, while secondary outcomes included walking gait and activities of daily living. Review Manager software (version 5.4.1) was used for data analysis. Results Among the 1,400 identified records, 12 eligible randomized controlled trials were finally included, with a total of 966 subjects. The results of the meta-analysis showed that the balance function of the experimental group and the control group was assessed using the Berg Balance Scale (MD = 4.87, p < 0.001, I2 = 90, 95% CI = 4.46–5.28). The motor function assessment of the experimental group and the control group used the Fugl-Meyer Motor Assessment (SMD = 1.11, p < 0.001, I2 = 94, 95% CI = 0.94–1.28) and Simple Test of Extremity Function (MD = 10.28, p < 0.001, I2 = 0, 95% CI = 7.89–12.68). Walking ability was measured using the Time-Up and Go Test (MD = −3.22, p < 0.001, I2 = 83, 95% CI = −3.71–−2.73). Activities of daily living were measured using the Modified Bathel Index (MD = 4.61, p < 0.001, I2 = 81, 95% CI = 3.61–5.61). Conclusion Initial evidence seems to show that Tai Chi Yunshou training can improve the balance and motor function of stroke survivors and further improve walking ability and daily living ability, and the rehabilitation effect may be better than that of conventional rehabilitation training. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=376969, identifier [CRD42022376969].